Hypertrophic Cardiomyopathy in South Western Nigeria - Mbakwem, Amam; Oke, David; Ajuluchukwu, Jayne (SA Heart Journal, 2017)
AIMS: To evaluate the prevalence of hypertrophic cardiomyopathy (HCM) and its characteristics (clinical, electrocardiographic and echocardiographic) in a hospital population presenting for echocardiography at the Lagos University Teaching Hospital (LUTH). MATERIALS AND METHOD: The echocardiographic records of patients over a two year period (1998-2000) were reviewed. Patients with a diagnosis of HCM were re-evaluated and included if they had a hypertrophied non-dilated left ventricle with maximal interventricular septum thickness ≥ 15mm and interventricular/posterior wall ratio >1.3 in the absence of any known cause of hypertrophy. RESULT: Fourteen (2%) of the 712 patients examined had hypertrophic cardiomyopathy with a male preponderance (M/F 3.7:1) and mean age of 43.14±15.00yrs. The commonest symptoms were chest pain and palpitations in about 50% of the subjects. Giant T wave inversion was present on the electrocardiogram of 42.9% of the subjects. The mean interventricular septum was 23.25±7.86mm (range 16 - 36mm) and the mean posterior wall thickness was 13.66±7.86mm (range 8.3 – 20mm). CONCLUSION: Hypertrophic cardiomyopathy occurs in about 2% of our population referred for echocardiographic examination. Hypertrophic cardiomyopathy should be considered in young males presenting with chest pain in Nigeria.